Hubungan Seks Lelaki sama Lelaki (Gay) dan Penularan Penyakit HIV/AIDS - Wahyu Pramono; Indraddin Indraddin; Dwiyanti Hanandini; Nini Anggraini; Zeni Eka Putri; Aziwarti Aziwarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
A correct understanding of sexual orientation can prevent community members exposure to male sexual behavior with men (Gay) and transmission of HIV/AIDS. Dedication aims to build awareness and commitment of village officials, community leaders and village cadres to take responsibility in preventing the transmission of HIV/AIDS through sexual relations between men and men (Gay). Community service activities were carried out in Nagari Batu Gadang Kuranji Hilir, Sungai Geringging District, Padang Pariaman Regency on 30-31 October 2019. The method of empowering village apparatus, community leaders, and village cadres with counseling and focus group discussions. The results of the activity showed that participants' understanding of the dangers of MSM sex and HIV/AIDS transmission increased and the growth of a shared commitment to prevent transmission of HIV/AIDS through MSM sex.